Quantitative and real-time evaluation of pressure on brain spatula with wireless and compact sensing system - Wang, Yongqing (2023)
The brain spatula has been an essential neurosurgical instrument since the early 20th century, when medical advancements enabled surgeons to operate deep intracranially for the first time. Monitoring the brain retraction pressure, especially at an early stage of the intradural procedure, is useful in preventing brain damage or postoperative cerebral swelling. Unfortunately, there is still a lack of effective methods that meet the demand for quantitative and real-time evaluation of applied pressure on brain tissue. In this study, a compact and wireless sensing system, encapsulated by soft biocompatible materials, for quantitatively assessing the pressure between brain tissue and a spatula, is proposed. The absence of physical tethers and the ion gel-based construction of the micro-structured sensor represent key defining features, resulting in high measurement accuracy of 1.0/N with reliable water-proof capabilities. Moreover, these sensors can be linked to a server network or mobile client for possible brain damage alerts as important safety addition. With our devices, detailed pressure data on retracting operations can be collected, analyzed, and stored for medical assistance as well as to improve surgery quality.